Pemberdayaan Ekonomi Masyarakat Desa Pemuda melalui Penguatan Akuntabilitas Keuangan BUMDes : Pengabdian - Muhammad Husni; Sumarno, Rafie Akbar; Fathony, Haris Reza; Anto Andreawan; Aldi, M. Fahriyal; Memey Ifalia Kristin; Rapy Ahmad Nazriel (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Strengthening the financial accountability of Village-Owned Enterprises (BUMDes) is key to enhancing rural community economic empowerment. This community service research was conducted in Desa Pemuda, Pelaihari Subdistrict. aiming to improve the capacity of BUMDes administrators in managing finances transparently and accountably. The activity applied a participatory approach and learning by doing, allowing participants not only to receive theoretical knowledge but also to engage directly in transaction recording and financial reporting practices. The implementation consisted of three main stages: (1) preparation and initial assessment, (2) training and mentoring, and (3) evaluation and follow-up. The results indicate significant improvement in the administrators’ understanding and skills in basic accounting, cash management, and financial reporting, along with increased awareness of transparency and accountability. Moreover, this mentoring strengthened BUMDes as a strategic institution to promote village economic independence. Based on these findings, it is recommended to conduct routine training, digitalize financial reporting systems, enhance community participation, and strengthen regulatory support from village authorities and related institutions.